Tuning three-dimensional textures with graphene aerogels for ultra-light flexible graphene/texture composites of effective electromagnetic shielding. (November 2015) - Song, Wei-Li; Guan, Xiao-Tian; Fan, Li-Zhen; Cao, Wen-Qiang; Wang, Chan-Yuan; Cao, Mao-Sheng
Abstract: For extending graphene aerogels for broad applications, here we demonstrate a simple and universal approach for scalable fabricating novel dual carbon three-dimensional (3D) hybrid structures, where the interspace of a 3D carbon texture has been modified by in situ generating graphene aerogels. Owing to the unique exceptional 3D carbon bi-frameworks of enhanced electrical conductivity and flexibility, the as-prepared graphene aerogel–carbon texture hybrid presents an ultra-light feature (0.07 g cm −3 in density), with highly effective electromagnetic interference (EMI) shielding performance up to 27 dB and 37 dB (in the X band region) at thicknesses of 2 and 3 mm, respectively. According to the mechanisms in EMI shielding, the fundamental criteria for evaluating a shielding material has been discussed and the excellent shielding performance coupled with the ultra-low density allows such 3D all-carbon hybrids to show more advantageous than the other carbon-based shielding composites. Implication of the results suggests that the strategy of various advantages could be widely extended to a variety of applications, promising a great platform for large-scale fabricating porous graphene-based materials into high-performance products.